FINANCIAL DISTRESS SEBAGAI PEMODERASI PENGARUH OPINI AUDIT GOING CONCERN PADA KETEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN - Wijayanthi, Putu Krisna; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This research aimed to get empirical evidence of the effect of going concern audit opinion and the ability to moderate the influence of financial distress going concern audit opinion on the timeliness of the publication of the financial statements of companies listed on the Stock Exchange Indonesia. The theory used in this study is the theory of the Agency (Agency Theory ). The population used in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the year 2012-2014. The samples used were 67 companies with purposive sampling technique. The data collection was conducted using non-participant observation. The data analysis technique used is the Logistic Regression Analysis and Moderated Regression Analysis (MRA). The results of this research showed that the variables going concern opinion of a negative effect the timeliness. Variable financial distress reinforce negative influence on the going concern opinion timeliness.
Keywords: going concern audit opinion, financial distress, timeliness